Assessment of the Perception of Librarians on Gender Stereotype as Correlate of Job Performance in Academic Libraries in Delta State - Olise Florence N. & Idoko Florence A., Nwose Lawrence O. (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2019)
Gender matters all over the world and in almost all areas of life. Librarianship is no exception. There exists obvious gender stereotypes in libraries all over the world. However, there is no empirical evidence that ascertains whether these gender stereotypes affect the job performances of librarians. This study therefore assesses the perception of librarians on gender stereotype as a correlate of job performance of librarians in academic libraries in Delta State. A structured questionnaire was used to survey 95 librarians in academic libraries in the State. Data were analyzed using percentages, descriptive statistics and Pearson moment correlation. Findings include that gender stereotypes exist to a low extent in these libraries and its influences have some negative sides on the job performances of librarians. However, it was found that there is no significant correlation between gender stereotypes and the job performance of librarians. Hence, recommendations were made.